INOVASI TEKNOLOGI BIOHIDROGEN DARI LIMBAH BIOMASA KE ENERGI LISTRIK DENGAN TEKNOLOGI FUEL-CELL - Rahman, Mahyudin Abdul; Dewi, Eniya (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Enterobacter aerogenes ADH-43, Bacillus pumillus Asp-8 and co-culture of bothmicroorganism was inoculated and fermented by using molasses as by product ofsugar factory, sugar starch, and glycerol as by product of biodiesel into hydrogen gas(H2). Both producing double mutant bacteria as a facultative anaerobe and who wasobtained by classical mutagenetically treated in order to enhance H2 producing. Wehave obtained that E. aerogenes ADH-43 has highest ability for molasses fermentation,and the volume H2 reached 4,0 l H2/l molasses.The fermentation was carried out in 50ml vial bootle, 37 oC, pH 5.8 and 20 hrs. Optimization of molasses concentration wasperformed in order to study the inhibition, and finally, 2 % of molasses was found. Toenhance the yield and H2 flow rate, the fed-batch system was applied into 6 l StirredTank Fermentor (STR). Innitial volume 2 l of medium was fermented, 1 l fresh mediumwas added into reactor at 6 and 9 hrs of fermentation time. Finally the achieved volumeH2 was 6,5 l H2/l molasses, the remained molases was 0,2 %, and the fermentationtime could be prolonged 4 hrs compare to bacth fermentation. We have also found therelationship between the H2 evolution rate and the voltage of electrical formed whenwe connected into 7 stack of fuel-cell.